Nucleic acid nano-carriers for delivery of antisense and RNAi therapeutics - Himanshu Sekhar Panda; Samraggi Choudhury; Jiban Jyoti Panda (Elsevier, 2024)
Nucleic acid nanotechnology presents an exciting approach for manufacturing tailored nanoscale biomaterials with precise structures, spatial precision, and exceptional biocompatibility. These nucleic acid-based nanomaterials, here referred as nano-carriers can have versatile applications in bio-imaging, diagnostics, and therapy. In this review, we have surveyed the progress made in the field of multifunctional nucleic acid nano-carriers, particularly in the context of delivering antisense and RNA interference (RNAi) therapeutics. RNAi technology has emerged as a potent modality for conducting functional genomic analyses and holds potential as an effective approach for crafting targeted gene-silencing treatments for viral infections, cancer, and other diseases in the future. Our focus is on exploring RNAi as a therapeutic avenue, taking into account challenges such as the expense of RNAi triggers, delivering RNAi efficiently to the target site, and addressing off-target and nontarget effects, while also recognizing promising opportunities within the field of biomedical research.